A Narratological Perspective on Installation Art. Issue 2 (2nd September 2021) - Combrink, Louisemarié
Abstract: Visual arts such as painting have been explored in the light of narratological concepts, but installation art has not received similar comprehensive narratological attention. The focus of the present article is to apply the four elements of narrative, namely time, space, character, and event, as conceptualised by Mieke Bal, to an exploration of a selection of visual artworks with an emphasis on installation art to demonstrate how the elements of narrative are thematised and foregrounded in installation art. These elements have to date not been consolidated into one publication on the visual arts. Special attention is paid to the installation artwork Baggage Arrival (2001) by the South African artist Jan van der Merwe, as an example of an artwork in which the four elements of narrative appear in a distinctive and thematised manner.